Route optimization method for BGP based on SDN in large-scale IP network - Hong TANG; Huahong ZHU; Weihua CAO; Jie ZOU (Dianxin kexue)
Aiming at rotation problem of route because of large-scale，multi-path，overlap in IP backbone networks，an optimization method for route reflection supported by both traditional routing devices and OpenFlow devices based on SDN controller technology was proposed.At first，the defects of traditional BGP routing mechanism was analyzed in detail.Then，a specific algorithm implementation and deployment scenarios were given.Test results of typical application scenarios demonstrate the validity of the proposed method.The average delay of international access reduces by 30%.